2022
DOI: 10.1136/bmj-2021-069052
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mRNA vaccines and waning of protection against SARS-CoV-2 infection and severe covid-19 during predominant circulation of the delta variant in Italy: retrospective cohort study

Abstract: Objectives To estimate the effectiveness of mRNA vaccines against SARS-CoV-2 infection and severe covid-19 at different time after vaccination. Design Retrospective cohort study. Setting Italy, 27 December 2020 to 7 November 2021. Participants 33 250 344 people aged ≥16 years who received a first dose of BNT162b2 (Pfizer-BioNTech) or mRNA-1273 (Moderna) vaccine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
99
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 28 publications
7
99
1
Order By: Relevance
“…Sex, age, comorbidities, and additional vaccine doses impact the risk of severe COVID-19 breakthrough illness. 10,[31][32][33] Among both PWoH and PWH, increasing age was the most significant risk factor for severe COVID-19 breakthrough illness in our study. Female PWoH had reduced risk, which has been previously documented; [34][35][36] however, female PWH had increased severe risk.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Sex, age, comorbidities, and additional vaccine doses impact the risk of severe COVID-19 breakthrough illness. 10,[31][32][33] Among both PWoH and PWH, increasing age was the most significant risk factor for severe COVID-19 breakthrough illness in our study. Female PWoH had reduced risk, which has been previously documented; [34][35][36] however, female PWH had increased severe risk.…”
Section: Discussionsupporting
confidence: 49%
“…Among PWoH, several comorbidities have been associated with increased severe COVID-19 breakthrough illness risk. 32,33,39 Our findings suggest an increased risk with HTN, ESRD, and SOT. Comorbidities were prevalent among those who experienced a severe COVID-19 breakthrough illness with 90% having a diagnosis of obesity, DM, HTN or ESRD.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Our findings are consistent with other studies investigating waning of vaccine effectiveness, as summarised through a systematic review by Feikin et al 21 Most observational studies employ a testnegative study design, while some are register-based cohort studies like ours. 19,[25][26][27][28][29][30][31][32][33] We reported large waning of effectiveness against SARS-CoV-2 infection, which could have several explanations. First, we have a longer follow-up time than previously published studies.…”
Section: Discussionmentioning
confidence: 99%
“…We also report on a reduction in VE against SARS-CoV-2 infection and COVID-19 related hospitalization and death for most evaluated vaccines in older adults and persons living with diabetes. Previous data had shown that waning of vaccine-induced immunity was associated with increased age and comorbidity 42 . Our observations of reduced vaccines effectiveness in people living with diabetes also supports previous evidence which reported reduced neutralizing antibody response and immunogenicity were observed in people with diabetes 43 .…”
Section: Discussionmentioning
confidence: 97%